Cell level flame containment of lithium-ion batteries - Wong, Rachael Lin (Nanyang Technological University, 2023)
This report evaluates the effectiveness and extent of various gas phase flame retardants (FRs) in containing the flame from a single pouch-cell lithium-ion battery (LIB) that has undergone TR. Additives tested are melamine, MgCO3, aluminium trihydrate (ATH), NaHCO¬3, sodium anthraquinone-2-sulfonate (AMS), anthraquinone and 4-aminophenyl sulfone (Dapsone). It was found that FRs that produce a high volume of gas on decomposition along with a high enthalpy of decomposition or sublimation, at more than 700 J/g was noticed to be able to effectively contain the single-cell TR, with a time to ignition (TTI) of more than 30 s through spark ignition, and 55 s through autoignition when tested on the cone calorimetry. Furthermore, it was found that the autoignition temperatures should also be taken into consideration when selecting an effective FR.